Evaluation of rodent models of osteoarthritis using lipidomic profiling and behavioural studies - Pousinis, Petros (2017)
Osteoarthritis (OA) is a complex, multifactorial, and slowly progressive disease where there is currently no effective medical treatment. Research in understanding the mechanisms of OA has been advanced by preclinical studies in rodent models of OA. Recent evidence highlights the role of different classes of lipids in OA pathogenesis. Therefore, the main aim of this thesis was to apply both targeted and untargeted (global) lipidomics mass spectrometry based an alytical methods, in conjunction with univariate and multivariate statistical analysis, in various tissues from three established rodent models of OA; meniscal transection (MNX), monosodium iodoacetate (MIA), and destabilization of the medial meniscus (DMM). The overall goal was to identify statistically differentiated lipids between controls versus OA rodents that may reflect changes in the pathophysiology of OA and associated pain. In addition, a global lipidomics workflow was developed by me, following the latest trends used within the wider metabolomics community, ensuring robustness and reproducibility in the identification of putative metabolite/lipid biomarkers for diseases.